Descriptive psychology - Brentano, Franz, 1838-1917 (International library of philosophy., 1995)
Franz Brentano (1838-1917) was a key figure in the development of 20th-century thought, influencing the work of philosophers such as Edmund Husserl. This work presents a series of lectures given by Brentano in 1887. It also provides a concise introduction which places Brentano within the history of philosophy and psychology and locates his influence in contemporary thought.